Analysis of Dry Reforming as direct route for gas phase CO2 conversion. The past, the present and future of catalytic DRM technologies. (March 2022) - le Saché, E.; Reina, T.R.
Abstract: Transition to low carbon societies requires advanced catalysis and reaction engineering to pursue green routes for fuels and chemicals production as well as CO2 conversion. This comprehensive review provides a fresh perspective on the dry reforming of methane reaction (DRM) which constitutes a straightforward approach for effective CO2 conversion to added value syngas. The bottleneck for the implementation of this process at industrial scale is the development of highly active and robust heterogeneous catalysts able to overcome the CO2 activation barrier and deliver sufficient amount of the upgrading products at the desired operation conditions. Also, its high energy demand due to the endothermic nature of the reaction imposes extra difficulties. This review critically discusses the recent progresses on catalysts design ranging from traditional metal-supported catalysts to advanced structured and nanostructured systems with promising performance. The main advantages and culprits of the different catalytic systems are introduced aiming to inspire the catalysis community to further refine these formulations towards the development of "supercatalysts" for DRM.  Besides the design of increasingly complex catalyst morphologies as well as other promising alternatives aiming at reducing the energy consumption of the process or tackle deactivation through reactor design are introduced.